PENGARUH GAYA KEPEMIMPINAN DAN DUKUNGAN TEMAN SEJAWAT TERHADAP MOTIVASI KERJA PEGAWAI PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG BANDA ACEH - Nasri Zarman; Eliana ilyas; Gunawan Gunawan; Teuku Andi Roza (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2023)
The aim of this study was to determine the influence of leadership style and peer support on employee motivation at the Public Works and Spatial Planning Office of Banda Aceh City, either partially or simultaneously. The number of samples in this study were 80 employees. This research method is a quantitative method. Research data was collected through a questionnaire. The research data were analyzed using multiple linear regression models and processed using the SPSS (statistical package for social science) assistance program. Hypothesis testing uses the t test and F test to find out the significant both partially and simultaneously. The results of this study are that there is a positive and significant influence between leadership style on employee motivation at the Public Works and Spatial Planning Office of Banda Aceh City with a tcount of 5.648 greater than a ttable of 1.991. In addition, there is also a positive and significant influence on the peer support variable on employee motivation at the Public Works and Spatial Planning Office of Banda Aceh City with a tcount of 2.727 greater than a ttable of 1.991. Based on the simultaneous test, it shows that the variables of leadership style and peer support have a significant effect on employee motivation at the Public Works and Spatial Planning Office of Banda Aceh City.